The Effect of Problem Based Learning by using Demonstration Method on The Ability of Problem Solving (Journal of Primary Education, 2018)
The purpose of this study was to determine the effect of PBL model by using the demonstration method on the problem-solving skills to elementary school students. The study applied quasy experimental research method with pretest-posttest control group design. The population of this study was the fourth grade students of Diponegoro cluster in Kudus, Central Java in the academic year 2017/2018. The samples taken for this study were the fourth grade students of SD 1 Kajeksan and SD 2 Demaan with the total number of 30 students for each school. The sampling technique used in this study was Nonprobability Sampling technique. The data collection technique applied in this study was test in the form of essay, as well as non-test technique which consists of observation and documentation. The data were analyzed by using gain score and t-test. The results showed that there is significant influence of PBL model by using demonstration method to student problem solving ability, this is supported by N-Gain result = 0.59 that is categorized as medium category. Then, pretest-posttest results of problem-solving ability by using PBL model with the demonstration method were tvalue = 7.667. Furthermore, there was a difference betwen students' ability in solving the problems by using PBL model within and without demonstration method (tvalue (3,801) > ttable (1,672)). This is supported by the result of observation to the student engagement which was 81.11%. It indicates that the PBL model by using demonstration method affects the problem solving abilities.